Studi Korelasi Aktivitas Listrik Udara Sebagai Prekursor Kejadian Gempabumi di Pidie Jaya: Abdi Jihad, Lori Agung Satria, Vrieslend H Banyunegoro, M Muhajir, Nasyithah Az-Zahra Lubis - Abdi Jihad Abdi Jihad; Lori Agung Satria Lori Agung Satria; Vrieslend H Banyunegoro Vrieslend H Banyunegoro; Muhajir Muhajir; Nasyithah Az-Zahra Lubis Nasyithah Az-Zahra Lubis (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2019)
Earthquake is a natural phenomenon that becomes an interesting topic to be studied. Precursors of an earthquake is a topic that had been long studied. This research aims to understand the relationship between Pidie Jaya earthquake and the electrical activity of the air. The data needed to conduct this research are electrical activity in the air that captured by LD2000, Himawari8 satellite data, and rainfall data obtained from GSMaP model. That relationship is obtained by calculating the correlation coefficient between those variables. The result shows that there is an increased in electrical activity two days before the event occurred. In order to reach the conclusion, the relationship between electrical activity in the air and rainfall correlation is calculated and it shows a negative value. This value means that there is a weak correlation between electrical activity in the air and rainfall. This weak correlation does not show up in the correlation between high rainfall and convective clouds growth.